Incorporating peace education into the school curriculum: building empathy and self-worth while taking ownership over peace - Lockwood, Markell (My University, 2014)
It is time for education to become pro-active in the support of teaching peace. There is an increased need for our education system to provide the skills to help our children become successful leaders in the future. This program was developed to teach peaceful vocabulary, give opportunities for peaceful leadership and practice, and to support peaceful problem-solving in an elementary school setting. The participants held weekly peace meetings and carried out activities that would encourage ownership over the program. Student surveys, student interviews, writing samples and parent testimonies were collected as evidence. Results indicated that student participants gained an understanding and heightened appreciation for peaceful vocabulary and how to look for goodness within others.
Plan B Paper. 2014. Master of Science in Education- Montessori--University of Wisconsin-River Falls. Teacher Education Department. 34 leaves. Includes bibliographical references (leaves 27-29).
Keywords: Peace--Study and teaching (Elementary--United States; Children and peace-Study and teaching--United States